District Level Information Systems: Two Cases from South Africa - Braa, J.; Heywood, A.; Shung King, M. (Methods of Information in Medicine, 1997)
The health system in South Africa has to date been fragmented and centralised. The priority of the new government is to establish an integrated and decentralised district health system of which a key element is the development of district health and management information systems (H & MIS). This paper presents experiences from two projects in the Western Cape in which a process to establish a district-based H & MIS was initiated and a situation analysis of the information systems was done. The two projects applied different research methods but the results show with remarkable consistency that much time is used on data collection, but information is not used at local level. The projects have applied different approaches towards developing a district H & MIS but in both important pre-requisites for a successful, action-led H & MIS include local ownership and motivation, a process based around existing local management structures and the active involvement of the community
Keywords: Health Information Systems; Management Information; District Health Systems